3D VQI: 3D Visual Query Interface - Uppalapati, S.; Femiani, J.C.; Razdan, A.; Gary, K. (2009 Sixth International Conference on Information Technology: New Generations, 2009)
The 3D Visual Query Interface (3D VQI) is a Web-based database application that allows for shape-based searches in addition to more traditional text-based queries of the 3D vessel dataset. This interface allows researchers remote access to vessel collection that can be analyzed from anywhere in the world. The interface is divided into two sections with right half supporting the ability to draw profile curve both symmetric and asymmetric. This query can be further refined using the left half which provides contextual based information. Using a curve-matching algorithm the software then searches the database and returns a series of potential matches sorted by the percentage of similarity between the curves. Each match can then be selected for more detailed viewing of the 3D model and data or for further analysis.